Ivy + Bean Make the Rules - Barrows, Annie; Blackall, Sophie (San Francisco, Calif. : Chronicle Books, 2012)
Seven-year-old Bean is too young to go to the camp her sister Nancy is attending, so she and her best friend Ivy decide to create their own camp.
Keywords: Ivy (Fictional character) -- Fiction; Bean (Fictional character) -- Fiction; Camps -- Fiction; Friendship -- Fiction